Analysis of disparity in income distribution and its relationship to consumption - a prospective study of a sample of employees - in Sulaymaniyah Governorate for the year 2023 (Raparin Journal of Humanities (RJH), 2024)
This research aims to clarify the basic features of both the disparity in income distribution and consumption, and then the impact of the disparity in income distribution on consumption for a sample of employees in Sulaymaniyah Governorate. In order to achieve this goal, we relied on the statistical analytical approach (deductive) based on data from a sample drawn from the research community. The research concluded that the disparity in income distribution between the community groups affected the level and type of consumption in Sulaymaniyah Governorate. Most of the sample members spend more than 300,000 dinars per month on food, while they spend less than 50,000 dinars per month on luxury goods, meaning that spending on food comes in first place, due to the low income levels in the Kurdistan Region, and the irregularity of employee income distribution periods, and then spending on health comes in second place. The study results also show an economic and statistical relationship between all study variables. This is due to the economic and financial conditions in the Kurdistan Region. At the end of the research, a set of proposals were presented, the most important of which is that the relevant authorities work to reduce the disparity in income distribution. In order to improve the standard of living, especially for the poor classes or strata. It also works to organize income distribution periods in a regular and organized manner. It is necessary for the government to work to reduce the level of unemployment and provide job opportunities in Sulaymaniyah Governorate in order to improve the level of income that affects the level of consumption for families.